Diante da morte ainda não somos todos modernos: O ideário do Bem Morrer e o Ethos Católico no Brasil - Torres, Valéria Aparecida Rocha (2018)
Introduction: The thought about O Bem Morrer is a relevant aspect in the construction of the sense of death and dying in Brazil. Systematized through manuals written mostly by Jesuit priests between XVII, XVIII and XIX centuries, where we find it as model of and for the death through the centuries and surpassing the binomial modernity/secularization that, by the end of the XIX century, became a characteristic of the Brazilian social and political life. Therefore, we try to understand the religious phenomena that provide this thought of Bem Morrer its longevity in the core of a society that, although claims itself as secular, results from a inneclesiamento process that characterizes the Brazilian Catholic ethos. Objective – explain and understand the longevity of the thought of bem morrer from invariables queries about death, represented through praxis and thinking involving the inneclesiamento characteristic of the Brazilian Catholicism. Methods – we elaborated a documentary group gathering three Bem Morrer manuals written between XVII and XVIII centuries by Jesuit priests Estevão de Castro, José Maria Bonucci and José Aires and a series of interviews within the Catholic community of Espírito Santo do Pinhal, SP. These were open and semi-structured interviews, following a pre-stablished guide about Catholic mortuary rites through remembrances and memories about religious coping with death. Invariables questions proposed by anthropologist Maurice Godelier were applied to the manuals and interviews, confirming the hypothesis that only religions can produce effective answers that support and provide meaning to the human existence. Results – It can be demonstrated that the invariable questions such as: Where do we go when we die? What to do on the last moment of life? - brought answers that changed little through centuries, having the ideals of bem morrer as a reference. Such longevity was possible due to the social life that was built around the Eclesia, main characteristic of the Brazilian society. This assumption was confirmed when many Catholic death rituals from different Brazilian regions were brought as a comparative element. From this, we could confirm that there is a Brazilian way of dying, expressed by the Catholic ethos and persisted above the social processes brought by the binomial modernity/secularization. Therefore, when facing death, we are all not moderns, yet